Booklet Cegah Stunting (BoCeSting) as an Educational Medium and its Influence on the Attitudes of Mothers Under Five on Stunting Prevention in the Archipelago - Dewi Mey Lestanti Mukodri; Rita Ridayani; Vina Jayanti (Alliance oh Health Activists (AloHA), 2022)
A major public health problem in developing countries, including Indonesia, is the nutrition problem. Nutritional problems in Indonesia are shown by the high prevalence of stunting, a chronic problem related to poverty, low education, inadequate services, and environmental health. One of the nutritional status problems in children under five is stunting, which is described as a form of growth failure due to poor nutrition and health during the prenatal and postnatal periods. One of the Efforts to reduce the incidence of stunting is by providing health education using media. Health education is part of health promotion to create community behavior conducive to health. The purpose of this study was to determine the effect of education using booklets (BoCeSting) on the attitudes of mothers under five about stunting prevention in the Archipelago region. This is a quantitative study using the quasi-experimental with pretest-posttest design. This study was only conducted in one intervention group. The population was mothers with toddlers aged 0-2. The research was located in Tanjungpinang City. The sampling technique in this study used a non-probability purposive sampling technique consisting of 74 respondents. The results showed that respondent attitudes in the moderate category increased to a good attitude (24 or 32.4%). The results of the attitude analysis showed (p-value = 0.000